Optical Imaging Techniques Applied to Dermatology - Amezcua-López, Erick Enrique; Corral-Martínez , Luis Francisco; Trujillo-Schiaffino, Gerardo; Salas-Peimbert, Didia Patricia; Anguiano-Morales, Marcelino (Revista Mexicana de Ingenieria Biomedica, 2024)
The use of optical imaging technology in recent years has improved diagnostics in the dermatology area. The techniques that can be named are optical coherence tomography, Raman spectroscopy, and optoacoustic imaging. Each technique has applications in general medicine and dermatology but with their respective limitations and focus. This work reviews the imaging techniques in general, prioritizing the theoretical background that allows the technique to operate, and then an image example obtained with the technique is shown. Then, an extensive review of the techniques of hyperspectral imaging and hyperspectral polarized dermatoscope is made. Finally, we talk about new trends in optical imaging future.